(untitled) (World Economics and Finance Bulletin, 2022)
For a long time under British influence, then under American influence, Iraq has an accounting system inspired by the Anglo-Saxon model, but the peculiarities imposed by the organization of the economy that come from history, make their mark on it. Analyzing the post-2003 period, we find that in terms of accounting policy innovation, the CPA and the Governing Council of Iraq have worked together to develop new accounting legislation, and the BSA and IBAAS have regulated the application of accounting standards in both the private and government sectors. that moment. Many writings in the literature state that the standards developed by IBAAS, also known as national standards (INAS), are convergent IFRS. Without rejecting this idea, given the historical context, as well as the divergent aspects between IFRS and US GAAP, we question the compatibility of the Iraqi accounting environment with IFRS and / or US GAAP and how strong is the link with each of these references, with all the more so as IUAS is based more on rules than principles.